Pemanfaatan Isolat Selulosa Ampas Tebu sebagai Chelating Agent (CAT) Zat Pewarna pada Jajanan Anak Sekolahan (JAS) - Romario Abdullah; Karmila Bilondatu; Wina Zulfiana Tulie; Wiwin Rewini Kunusa (Jambura Journal of Chemistry, 2019)
This study aims to detect synthetic dyes in JAS (School Children Snacks) using a chelating agent (CAT) from bagasse waste. Instrumentation used in the analysis was spectronic 20D. Sugarcane pulp cellulose products as CAT adsorbent rhodamine B coloring agent, metanil yellow and tartrazine in JAS were applied to 10 types of soft drink samples circulating in the market in Gorontalo City. The method used is the adsorption method. The adsorption capacity produced by cellulose with 75% content and α-cellulose content was 37.8% for sample 1 (56%) sample 2 (12%), sample 3 (83%), sample 4 (54%), sample 5 (45%) , sample 6 (54%), sample 7 (51%), sample 8 (27%), sample 9 (69%) and sample 10 (25%). The adsorption capacity produced by cellulose was 88.4% and α-cellulose content was 45.2% for sample 1 (56%) sample 2 (12%), sample 3 (83%), sample 4 (54%), sample 5 (45%) , sample 6 (54%), sample 7 (51%), sample 8 (27%), sample 9 (69%) and sample 10 (25%).